2017
DOI: 10.12816/0038790
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Use of Electronic Information Resources by Medical Students at Al-Jouf University in Saudi Arabia

Abstract: Electronic resources are becoming an integral part of the modern education system, especially in higher education settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Awareness of EIRs is a facilitator for using these resources in the library; the findings from this study suggest that the users of electronic resources at Muni and Lira Universities are aware of the various EIRs provided to them. This outcome is consistent with the studies conducted by 15,[32][33][34]38 who noted that teaching staff were aware of the e-resources, although the usage of these resources remained low. However, this observation contradicts a similar study by Gakibayo et al (2013).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Awareness of EIRs is a facilitator for using these resources in the library; the findings from this study suggest that the users of electronic resources at Muni and Lira Universities are aware of the various EIRs provided to them. This outcome is consistent with the studies conducted by 15,[32][33][34]38 who noted that teaching staff were aware of the e-resources, although the usage of these resources remained low. However, this observation contradicts a similar study by Gakibayo et al (2013).…”
Section: Discussionsupporting
confidence: 91%
“…For example, the survey conducted by Leonard et al (2020) 15 on electronic resources by law academics at the University of Namibia found that 100% of the Law faculty members were aware of the e-resources subscribed to, although the usage of the resources remained low. The studies by Yebowaah (2017), 32 Ahmed and Al-Reyaee (2017), 33 and Adeleke and Nwalo (2017) 34 reported that the majority of the users were aware of electronic resources and also highlighted the benefits of the awareness of EIRs to the academic community. Similarly, Ncube and Tarumbira (2016) 35 studied using e-resources at the Zimbabwe Open University Midlands Library.…”
Section: Electronic Information Resources Awareness In Academic Libra...mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Ali stopped his Arabic search when he was not successful in finding the desired resources. Ali’s experience is similar to that of participants in a study by AlRiyaee and Ahmed (2017): those participants turned to general search engines when they failed to find electronic resources via the library portal at Al-Jouf University.…”
Section: Discussionmentioning
confidence: 57%